The recent changes in ISO standards in connection with certifi cation of medical products - Borek-Wojciechowska, Regina; Kłokow, Sylwia (Polish Journal of Public Health, 2009)
ISO standards established a signifi cant phase of chan ges in the attitude towards the quality. The standards were applied in order to create systems which provide and monitor the quality in many organizations. The systems were used to prepare standards dealing with quality management systems taking in consideration specifi c demands of the trade for which they were designed, for example: QS 9000, AS 9000, TL9000. The standards were also applied in the EU to certify goods in the process of the CE sign granting. In the article which is the fi rst part of the discussed issue the changes in the ISO 9000 series are presented. The changes were the effect of the update of the standards and their signifi cance in modular conception adopted in the EU in connection with the CE sign.